Multiejector CO2 cooling system with evaporative gascooler for a supermarket application in tropical regions. (25th May 2021) - Singh, Simarpreet; Hafner, Armin; Maiya, M.P.; Banasiak, Krzysztof; Neksa, Petter
Highlights: Multiejector trans-critical CO2 cooling system (33 kW) is tested at high ambient temperature upto 46 °C. Improvement in COP with IHX and evaporative cooler is 11% and 40% respectively. Reduction in PIR with IHX and evaporative cooler is 8.5% and 26% respectively. Study project the compatibility of an evaporative condenser with the ejector-based CO2 cooling system. Abstract: In the present study, the performance of a 33 kW multiejector trans-critical CO2 cooling system is experimentally evaluated for a supermarket application with/without internal heat exchanger and evaporative cooling. In order to enhance the overall performance of the system for tropical regions, the testing is carried out at high ambient temperature (up to 46 °C) with 5 cm, 10 cm and 15 cm cooling pad thickness arrangements. The experimental results clearly projects that the evaporative cooler capacity reaches a maximum of 10 cm pad thickness. However, a minor improvement is observed in terms of Coefficient of Performance and Power Input Ratio beyond 10 cm pad thickness. Maximum improvement in COP with internal heat exchanger and evaporative cooler is 11% and 40% respectively. On the other hand, a maximum reduction in the system Power Input Ratio with internal heat exchanger and evaporative cooler is 8.5% and 26% respectively. However, a minor enhancement in Coefficient of Performance and Power Input Ratio of 4% and 6% are observed respectively with 15 cm cooling pad thickness. Furthermore, a comparative analysis is carried out with the existing and present experimental study to project the compatibility of an evaporative condenser in the ejector based CO2 cooling system. From the study, it is evident that the evaporative cooling arrangement for the gascooler of the CO2 system is suggested as a potential solution to the supermarket application at a high ambient temperature context.